FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN IBU HAMIL DALAM MELAKUKAN KUNJUNGAN ANTENATAL CARE (ANC) DI PUSKESMAS REWARANGGA - Anatolia Karmelita Doondori; Maria Salestina Sekunda (Poltekkes Kemenkes Kupang, 2022)
Antenatal Care is a planned program in the form of observation, education and medical treatment in pregnant women, to obtain a process of pregnancy and childbirth that is safe and satisfying. The purpose of this research is to know the factors influencing the non-compliance of pregnant mother in doing Antenatal Care (ANC) visit at Rewarangga Health Center.Type of descriptive research with survey research design. The population of all pregnant women who did not make an Antenatal Care visit in January of 2016 which amounted to 60 people. The sampling technique is the total population, so the sample number is 60 people. The results of the study indicated that the educational factors influenced and also did not affect 50 people (50%) in the ANC visit, the knowledge factor influenced 54 people (90%) in the ANC visit and the occupational factors did not affect 56 people (93%) in the ANC visit, health support factors did not affect 58 people (97%) in ANC visits and husband and family support factors affected 42 people (70%) in ANC visits. The conclusion is that the knowledge factor (90%), husband and family support factor (70%) are factors influencing non-adherence of pregnant mother during Antenatal Care visit. It is recommended that health workers always provide health education to pregnant women about the importance of doing examinations during pregnancy. Nurses/midwives are expected to further improve their skills and always provide friendly service. Friendly service will indirectly increase the passion of the community in this case pregnant women to visit health facilities.